The Utilization Of Some Of Biochar To Retain N-Total In Inceptisols - Ulfa Heryani; Benny Hidayat; Mukhlis (Jurnal Pertanian Tropik, 2018)
Nitrogen is very important nutrient growth of plant but eassy lost from soil. The aim of this researc to get the best biochar feedstock in maintaining N-total in the Inceptisol soil. Theresearch was carried out in the laboratory using the method of experiment. This research was carried out with complete randomized design non factorial with the treatment without biochar (controls), and 4 types of biochar from palm empty fruit bunches, rice straw, rice husks and wood, is repeated four times. The observed parameters are pH H2O,CEC, & N-total ground. The results showed that the four types of biochar can increase the pH H2O, CEC, N-total ground. Loss of Nutrient N decreased significantly due to the granting of biochar palm empty fruit bunches. Absorption capacity of biochar to reduce leaching of N in the soil of inseptisol sorted from largest to smallest is biochar palm empty fruit bunches, rice husk, rice straw and wood.